Evaluating the Efficacy of Convolutional Neural Networks Across Diverse Datasets - Gupta, swati; Bal Kishan; Pooja Mittal (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
Focusing on sentiment analysis and medical image processing, this paper assesses Convolutional Neural Networks performance across different datasets. Emphasized are recent developments in deep learning models for segmentation and picture categorization as well as other purposes. Using contemporary Convolutional Neural Network architectures, this work seeks to get good performance in medical diagnosis and sentiment analysis. The paper emphasizes how well Convolutional Neural Networks perform in domain-specific tasks. Using the same data preparation techniques, appropriate designs, and strategies to split the data, this paper investigates how well Convolutional Neural Network algorithms perform on medical data and sentiment analysis. Convolutional Neural Network models are optimized using hyperparameter tweaking and cross-validation techniques. While guaranteeing patient privacy, data anonymization, and bias reduction, the research seeks to highlight strengths, weaknesses, and patterns. Focusing on ethical concerns and offering suggestions for improvement, it tackles problems in sentiment categorization and medical imaging anomaly detection. This work attains 96 percent accuracy using Convolutional Neural Networks across four datasets. Common measures in the performance assessments of Sentiment Analysis, Skin Cancer Detection, Brain Tumour Detection, and Kidney Stone Detection include F1 scores, recall, and accuracy. With 0.97, Brain Tumour Detection had the highest accuracy; Kidney Stone Detection and Skin Cancer Detection both had 0.95; Sentiment Analysis scored 0.96. The consistently high recall and accuracy scores across all domains indicate good classification capabilities; an F1 score between 0.95 and 0.96 guarantees outstanding performance in both detection and analysis tasks.